2016
DOI: 10.1111/1754-9485.12504
|View full text |Cite
|
Sign up to set email alerts
|

The value of spectral imaging to reduce artefacts in the body after 125I seed implantation

Abstract: Gemstone spectral imaging technique can reduce metal artefacts of I seeds effectively in CT images, and improve the quality of images, and improve the display of tissues adjacent to I seeds after implantation. MARs technique cannot reduce the artefacts caused by radioactive seeds effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Another study revealed that VMI combined with MAR significantly increased the CNR of images following 125 I seeds implantation. The optimal SNR and CNR values were achieved at VMI 80 keV( 4 ). The disparity between the optimal VMI keV level in our study and previous literature suggested significant differences in the spectral imaging methods utilized in the 2 studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study revealed that VMI combined with MAR significantly increased the CNR of images following 125 I seeds implantation. The optimal SNR and CNR values were achieved at VMI 80 keV( 4 ). The disparity between the optimal VMI keV level in our study and previous literature suggested significant differences in the spectral imaging methods utilized in the 2 studies.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that the AI value initially increased and then decreased as VMI keV increased. The lowest AI value was achieved at a virtual monoenergetic level of 80 keV ( 4 ). Another study focused on artifact reduction after 125 I seeds implantation revealed that the average SD value and AI value of artifact images decreased as VMI keV increased ( 3 ).…”
Section: Discussionmentioning
confidence: 99%